Propagation and nominal inflection in some Central-Southern Italian dialects (Atti del Sodalizio Glottologico Milanese, 2017)
The article investigates the phonological process known as propagation, well attested in Central-Southern Italian dialects: the process can be described as the development of a non-etymological glide where are copied some features of an high vowel (or a glide) placed in an adjacent syllable. The manifestations of such a change in two dialects of the Southern Italy are illustrated: San Donato and Terelle, both settled in Val di Comino, in southern Lazio. Considerations on the phonological properties involved and the morphologisation of the process are developed. KEYWORDS: phonology, propagation, phonological change, nominal inflection, Central-Southern Italian dialects